Teachers' and Students' Thinking of Traditional and Cooperative Learning - Beresnevičienė, Danguolė; Teresevičienė, Margarita (Acta Paedagogica Vilnensia, 1997)
The central focus of the paper is university teachers and student-teachers' thinking about traditional and cooperative learning at universities. This is quite a new method of learning in Lithuanian universities. 45 students-teachers seeking a Master's degree and 15 university teachers holding Doctorate degrees anonymously completed a Semantic Differential type scale which asked them to rate traditional and cooperative learning in terms of 19 bipolar rating factors. The data indicates that students-teachers as well as university teachers think more positively about teaching and learning in groups than in traditional lectures. This difference was significant (p < 0.01). Both groups of participants evaluated cooperative learning as mare "active'', "creative", "friendly", "democratic'', and "responsible" than traditional learning and teaching. Contrary to the students, university teachers thought that cooperative learning was more "difficult" than traditional learning (p < 0.05).
Keywords: teaching; learning; cooperative learning; university teachers; university students